DINAMIKA MONEY POLITICS PADA PEMILUKADA ACEH 2017 - Januar, Eka (Al-Ijtima`i: International Journal of Government and Social Science, 2018)
In this contemporary times, elections or direct regional head elections (local elections) are considered to be one of the most appropriate ways to conduct regular elections or changes of power, therefore a good local election must prioritize justice and democratic principles which away from fraudulent behavior such as money politics. In the Aceh local election in 2017, it is suspected that there have been many practices of money politics in some areas and and if it real happened it would be not good for the development of democracy. Moreover, since Aceh is an area that implements Islamic law, so money politics is intolerable which in Islam itself the behavior of money politics is included in bribery cases which are certainly not justified in Islam. This study tried to examine the dynamics of money politics in the 2017 Aceh local election. The type of reseach is descriptive qualitative that aims to provide an overview and explanation of the variables studied. The theory used in this study is the Rational choice theory popularized by James S, Coleman. The results of this study indicate that the practice of money politics was occured and practiced by almost all candidates with various motives as if it were not money politics. There were including giving basic food coupons or in the form of public facilities so that people are not aware of what they receive is also money politic